2017
DOI: 10.1038/nmicrobiol.2017.67
|View full text |Cite|
|
Sign up to set email alerts
|

Convergent evolution of a modified, acetate-driven TCA cycle in bacteria

Abstract: The tricarboxylic acid (TCA) cycle is central to energy production and biosynthetic precursor synthesis in aerobic organisms. There exist few known variations of a complete TCA cycle, with the common notion being that the enzymes involved have already evolved towards optimal performance. Here, we present evidence that an alternative TCA cycle, in which acetate:succinate CoA-transferase (ASCT) replaces the enzymatic step typically performed by succinyl-CoA synthetase (SCS), has arisen in diverse bacterial group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 19 publications
0
42
0
Order By: Relevance
“…Rather, our metaproteomics data suggested that taxa within Firmicutes and to a minor extent in Bacteroidetes, Proteobacteria and Verrumicrobia employed a variation of the classical TCA cycle based on an unorthodox enzyme, acetate:succinate CoAtransferase (ASCT) to synthesize succinyl-CoA. Kwong et al recently showed that ASCT genes were widespread in prokaryotic genomes and functionally replaced SCS in TCA cycle of human microbial commensals (Kwong et al, 2017). In a carbon-rich anaerobic gut ecosystem, this strategy may be a result of niche specialization where gut microbiota may use acetyl-CoA, the keystone molecule of central metabolism produced from monosaccharides, amino acids, fatty acids and other secondary metabolites, as driver of a reverse TCA cycle to maintain redox balance and obtain energy for growth.…”
Section: Metabolic Signatures Differentiate Chronological States Of Imentioning
confidence: 81%
See 1 more Smart Citation
“…Rather, our metaproteomics data suggested that taxa within Firmicutes and to a minor extent in Bacteroidetes, Proteobacteria and Verrumicrobia employed a variation of the classical TCA cycle based on an unorthodox enzyme, acetate:succinate CoAtransferase (ASCT) to synthesize succinyl-CoA. Kwong et al recently showed that ASCT genes were widespread in prokaryotic genomes and functionally replaced SCS in TCA cycle of human microbial commensals (Kwong et al, 2017). In a carbon-rich anaerobic gut ecosystem, this strategy may be a result of niche specialization where gut microbiota may use acetyl-CoA, the keystone molecule of central metabolism produced from monosaccharides, amino acids, fatty acids and other secondary metabolites, as driver of a reverse TCA cycle to maintain redox balance and obtain energy for growth.…”
Section: Metabolic Signatures Differentiate Chronological States Of Imentioning
confidence: 81%
“…Kwong et al . recently showed that ASCT genes were widespread in prokaryotic genomes and functionally replaced SCS in TCA cycle of human microbial commensals (Kwong et al ., ). In a carbon‐rich anaerobic gut ecosystem, this strategy may be a result of niche specialization where gut microbiota may use acetyl‐CoA, the keystone molecule of central metabolism produced from monosaccharides, amino acids, fatty acids and other secondary metabolites, as driver of a reverse TCA cycle to maintain redox balance and obtain energy for growth.…”
Section: Resultsmentioning
confidence: 97%
“…How bacterial activities in the bee gut impact the host or gut environment has so far remained elusive except for a few cases. For example, the microaerophilic core member S. alvi has been implicated in maintaining anoxic conditions in the ileum [18] by respiring oxygen via an alternative citrate cycle driven by acetate [23,53,54]. Interestingly, acetate is one of the major fermentation products generated by G. apicola, which together with S. alvi forms a multispecies biofilm on top of the host epithelium, from where the oxygen may be released.…”
Section: Functional Roles Of Individual Speciesmentioning
confidence: 99%
“…In addition to the variation within the individual reactions, per se , there are other variations of note, not least of which being the Anon‐Buchanan cycle, in which the TCA cycle runs in the reverse direction in a wide range of bacteria (Buchanan et al ). There are also a range of shunts and bypasses which occur in non‐plant systems, including the citramalate shunt (Filatova et al ), the bypass of the 2‐oxoglutarate dehydrogenase reaction uncovered recently in cyanobacteria (Zhang and Bryant ; Steinhauser et al ), and the recently described acetate shunt (Kwong et al ), as well as variants of the glycoxylate shunt (Vuoristo et al ) which is confined to specialized peroxisomes, known as glycoxysomes in plants and absent in mammals. A maleate shunt has also been described in several bacteria and the compound is detectable in plants and correlates with levels of malate and fumarate, yet the genes/enzymes responsible have not yet been characterized in plants (Sweetlove et al ; Sweetlove et al ).…”
Section: Perspectives For Synthetic Biology Approaches At Modifying Tmentioning
confidence: 99%